2021
DOI: 10.1108/ejm-01-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

How preexisting beliefs and message involvement drive charitable donations: an integrated model

Abstract: Purpose The purpose of this paper is to investigate how individuals respond to messages asking for donations in broadcast advertising. It does so by considering both preexisting attitudes and beliefs related to donating, as well as message processing. The goal is to uncover messages that may help nonprofit organisations increase donations. Design/methodology/approach The research combines the theory of planned behaviour (TPB) to measure preexisting beliefs and the elaboration likelihood model (ELM) to measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 137 publications
0
7
0
Order By: Relevance
“…Identifying specific characteristics of an individual or situation that can affect involvement may lead to strategies that can influence an increase or decrease in level of involvement (Day et al, 1995 ) and ultimately affect donation intention. This is because strategically targeting audiences based on involvement may lead to better fundraising results (Grau & Folse, 2007 ; Van Steenburg & Spears, 2021 ). Nonprofit marketing managers need to understand audience involvement by determining what is personally relevant to them in terms of a brand, behavior, event, situation, social environment, or a combination of those in order to develop the best strategies and tactical executions (Peter & Olson, 1994 ).…”
Section: Future Fundraising Strategies and Marketing's Rolementioning
confidence: 99%
See 4 more Smart Citations
“…Identifying specific characteristics of an individual or situation that can affect involvement may lead to strategies that can influence an increase or decrease in level of involvement (Day et al, 1995 ) and ultimately affect donation intention. This is because strategically targeting audiences based on involvement may lead to better fundraising results (Grau & Folse, 2007 ; Van Steenburg & Spears, 2021 ). Nonprofit marketing managers need to understand audience involvement by determining what is personally relevant to them in terms of a brand, behavior, event, situation, social environment, or a combination of those in order to develop the best strategies and tactical executions (Peter & Olson, 1994 ).…”
Section: Future Fundraising Strategies and Marketing's Rolementioning
confidence: 99%
“…Recent research has found that those who are involved in an advertisement and have a positive attitude toward charitable giving are going to donate if they are told that others support the cause (Van Steenburg & Spears, 2021 ). Messages targeting those not involved with the ad but still believe giving is appropriate behavior, may turn them into donors if coupled with messages about community support for the NPO.…”
Section: Future Fundraising Strategies and Marketing's Rolementioning
confidence: 99%
See 3 more Smart Citations